PENGARUH PROFITABILITAS, CAPITAL INTENSITY, DAN INVENTORY INTENSITY TERHADAP EFFECTIVE TAX RATE - Eva Fauziah Ahmad (MAKSI, 2018)
Efective tax rate is the amount of tax expence that must be paid by tax subject in a reasonable amount so taht is does not impede the achievement of the tax subjec. The purpose of this study is to determine and analyze the effect of profitability, capital intensity, and inventory intensity agains efective tax rate this study uses secondary data taken from the annual financial statement of manucturing companies industrial sector of custumer goods listed in Indonesia Stock Exhange 2013-2017.Based on research result pathally profitability doesn’t affect efective tax rate, meanwhile capital intensity and inventory intensity affect the efective tax rate. While simultareously profitability, capital intensity and inventory intensity affect the efective tax rate.Keywords: profitability, capital intensity, inventory intensity ,effective ta tax rate